(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
In this article, the existing highways in the Republic of Uzbekistan and their classification, distribution by road categories, the status and processes of formation in the geodatabase are reflected. At the same time, the classification of highways according to the amount of future traffic, the state registration of highways and their share in the importance of their use are described.